Improving Sweet Bread Properties with Diacetyl Tartaric Acid Ester of Monoglyceride (DATEM) - Yoga Pratama; Felda Pamella Hardiyanti; Antonius Hintono (Diponegoro University, 2024)
Diacetyl Tartaric Acid Ester of Monoglyceride (DATEM) has been used in bread making to improve its dough and final product properties. The efficiency of DATEM in bread with the presence of sugar is yet to be studied. Therefore, this study aims to examine the effects of DATEM addition on sweet bread properties, i.e., its water content, loaf volume expansion, porosity and organoleptic properties. Completely Randomized Design (CRD) was employed with 5 treatments and 4 replications. The variables were the addition of DATEM, i.e., 0%, 0.15%, 0.3%, 0.45%, 0.6% (w/w) of the total flour. The data were analyzed using Analysis of Variance (ANOVA) with the significance level of 5%. The study showed that DATEM significantly impacts the physical and organoleptic properties of sweet bread. As DATEM concentration increases, so does moisture content, porosity, and loaf volume. Consequently, the texture becomes softer, and fewer crumbs are produced. Overall, DATEM enhances sweet bread properties, with 0.6% concentration yielding the best results. Sweet bread with 0.6% DATEM exhibited 34.05% moisture content, 76.86% loaf volume expansion, and 3.38 mm porosity.